ANALISIS DAN PERANCANGAN SITEM INFORMASI PENJAMINAN MUTU STANDAR PENDIDIKAN DAN PENGAJARAN PADA STMIK DCI TASIKMALAYA - Sarmidi Sarmidi; Sutarman Sutarman (UNIVERSITAS RAHARJA, 2018)
The quality assurance system at STMIK DCI Tasikmalaya is now started with the determination of policies, standards, manuals, and form documents. Only in the implementation is not supported by information systems, so the process of socialization of policies, standards, manuals, and is not effective and may result in limited access for the parties in need. In addition, in the implementation of monitoring and evaluation (Monev) the standard documents of education and teaching also became less efficient and can hamper the implementation of internal quality assurance system. To that end, then created a prototype web-based quality assurance information system for STMIK DCI Tasikmalaya and modeled it using UML. With the prototype of quality assurance information system is expected to assist the implementation of quality assurance system for the STI Tasikmalaya DCI to improve the quality of the institution.